Shear-Regulated Extracellular Microenvironments and Endothelial Cell Surface Integrin Receptors Intertwine in Atherosclerosis - Mo, Fan-E (Frontiers in Cell and Developmental Biology, 2021)
Mechanical forces imposed by blood flow shear stress directly modulate endothelial gene expression and functional phenotype. The production of extracellular matrix proteins and corresponding cell-surface integrin receptors in arterial endothelial cells is intricately regulated by blood flow patterns. Laminar blood flow promotes mature and atheroresistant endothelial phenotype, while disturbed flow induces dysfunctional and atheroprone endothelial responses. Here, we discuss how hemodynamic changes orchestrate the remodeling of extracellular microenvironments and the expression profile of the integrin receptors in endothelial cells leading to oxidative stress and inflammation. Targeting the interaction between matrix proteins and their corresponding integrins is a potential therapeutic approach for atherosclerosis.